APLIKASI PENGOLAHAN DATA NILAI SISWA SEKOLAH DASAR NEGERI 07 PONDOK BAMBU BERBASIS WEB - Gita Hamidah (2023)
In this modern era, the use of technology is increasingly being implemented as a data collection process in various fields, one of which is in the school sector. In this study, the authors discuss the Student Grade Data Processing Application at State Elementary School 07 Pondok Bambu which is still manual and does not yet have a website-based information system. So in this study the authors will design a Web-Based Student Grade Data Processing Application which aims to facilitate Sekolah Dasar Negeri 07 Pondok Bambu in delivering information and processing and collecting assessment data to reporting and making it easier for parents of students to access information. The programming language applied in building applications uses PHP using the MySQL database management system and in running the server is assisted by the XAMPP application.